ANALISIS PENGGUNAAN MAJAS SIMILE PADA NOVEL “BUMI CINTA” KARYA HABIBURRAHMAN EL SHIRAZY - Ema Erviyana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Abstract The novel is one of the literary works that can be used as a forum for writers to express their ideas and ideas. The choice of diction and sentence structure and the use of speech in writing novels will be able to provide more interesting values and the writer's message is conveyed very well. The purpose of this study was to determine the use of simile forms in the novel "Bumi Cinta" by Habiburrahman El Shirazy by using stylistic studies. This research study uses data analysis techniques on the research object by reading the novel "Bumi Cinta" as a whole, understanding the contents of the novel, then finding words that contain simile in each sentence in the novel and describing it. From the research results of stylistic analysis on the novel "Bumi Cinta" shows that the novel contains a lot of simile forms.